The hormone replacement therapy and the diseases of the arteries - Dębski, Romuald (Menopause Review/Przegląd Menopauzalny, 2006)
The influence of the hormone replacement therapy on the development of the diseases of the cardiovascular system has been investigated since the 1980s. In spite of the early positive outcome, two large studies, HERS and Nurses Health Study, proved that the therapy was ineffective regarding secondary prevention. Another study, the WHI, showed that the risk of a cardiac infarct was significantly lower if the hormone replacement therapy consisted only of estrogen and was introduced within 10 years after the menopause. Doctors were also in search of the optimal way of applying the therapy in order to avoid its complications, however the rules that they came up with were often inconsistent with the scientific findings. It was recommended that the indications for the replacement therapy be narrowed down. Moreover, a short-term therapy was advised, managed with lowdose medications where the hormone levels in serum were remarkably lower than those observed during regular ovarian cycles despite the lack of evidence that this was an advantage. At present it is considered that it is best to begin the hormone replacement therapy in perimenopause using the smallest effective doses. The idea of rigid time limits has been abandoned. The transdermal way of administering this therapy is also the source of a beneficial influence of the therapy on the serum levels of the C-reactive protein, the D-dimers and also adhesive substances which play an important role in the pathogenesis of atherosclerosis. An additional profit of using the parenteral way is the lack of activation of coagulation factors and the absence of the unfavourable effect on the level of triglycerides.